The Effect of the Interdependence of the Corporate Governance Mechanism on Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange - Ena Rosita; Raden Arief Wibowo (Accounting and Finance Studies, 2021)
This study aims to examine the effect of interdependence mechanisms of corporate governance on company engaged in the Indonesia stock Exchange 2012-2015. These mechanisms are: managerial ownership, institutional ownership, independent commissioner, board size, debt policy, dividend policy, market concentration, and market share. The sample used in this research is secondary data as much as 96 company annual report with purposive sampling method and data analysis technique used is multiple linear regression analysis. The results of this study are only significant institutional ownership variables to the company